Is Pathfinder a safe alternative to the emergency department for older patients? An observational analysis. (9th June 2021) - Bernard, Paul; Corcoran, Grace; Kenna, Lawrence; O'Brien, Claire; Ward, Peter; Howard, William; Hogan, Laura; Mooney, Rebecca; Masterson, Siobhan
Abstract: Background: many patients brought to emergency departments (EDs) following an emergency medical services (EMS) call have non-urgent needs that could be treated elsewhere. Older people are particularly vulnerable to adverse events while attending the ED. Alternative care pathway models can reduce ED crowding and improve outcomes. Internationally, there is no consensus on which model is recommended. Aim: the aim of this study is to investigate the impact of the Pathfinder model on ED conveyance rates and patient safety. Methods: the Pathfinder service is a collaboration between the National Ambulance Service and Beaumont Hospital Occupational Therapy and Physiotherapy Departments. It is supported by the Government of Ireland's Sláintecare Integration fund. This is a retrospective cohort study of the Pathfinder service over a 5-month period. Results: one-hundred and seventy-eight patients were responded to by the Pathfinder 'Rapid Response Team'. Average age was 79.6 years (standard deviation 7.6), median clinical frailty score was 6 (interquartile range: 5–6). Sixty-four percent remained at home following initial review. None re-presented to the ED within 24 hours, and 10% re-presented within 7 days. The majority (67%) of patients required follow-up by the Pathfinder 'Follow-Up Team' and/or another community-based service. Feedback demonstrates 99% patient satisfaction with the service. Conclusion: the Pathfinder service is a safe alternative to ED conveyance for older people following an EMS call. It is the first model of this kind to be evaluated in Ireland. The overwhelmingly positive feedback confirms that older people want this service. This model could expand, with local adaptation, nationally and internationally.